Whole-Genome Survey Analyses Provide a New Perspective for the Evolutionary Biology of Shimofuri Goby, Tridentiger bifasciatus - Xiang Zhao; Yaxian Liu; Xueqing Du; Siyu Ma; Na Song; Linlin Zhao (Animals, 2022)
The shimofuri goby (Tridentiger bifasciatus) is a small and highly adaptable goby, distributed along the coasts of China, the Sea of Japan, and the west coastal and estuarine areas of the Northwest Pacific. Next-generation sequencing was used to generate genome-wide survey data to provide essential characterization of the shimofuri goby genome and for the further mining of genomic information. The genome size of the shimofuri goby was estimated to be approximately 887.60 Mb through K-mer analysis, with a heterozygosity ratio and repeat sequence ratio of 0.47% and 32.60%, respectively. The assembled genome was used to identify microsatellite motifs (Simple Sequence Repeats, SSRs), extract single-copy homologous genes and assemble the mitochondrial genome. A total of 288,730 SSRs were identified. The most frequent SSRs were dinucleotide repeats (with a frequency of 61.15%), followed by trinucleotide (29.87%), tetranucleotide (6.19%), pentanucleotide (1.13%), and hexanucleotide repeats (1.66%). The results of the phylogenetic analysis based on single-copy homologous genes showed that the shimofuri goby and Rhinogobius similis can be clustered into one branch. The shimofuri goby was originally thought to be the same as the chameleon goby (Tridentiger trigonocephalus) due to their close morphological resemblance. However, a complete mitochondrial genome was assembled and the results of the phylogenetic analysis support the inclusion of the shimofuri goby as a separate species. PSMC analysis indicated that the shimofuri goby experienced a bottleneck event during the Pleistocene Glacial Epoch, in which its population size decreased massively, and then it began to recover gradually after the Last Glacial Maximum. This study provides a reference for the further assembly of the complete genome map of the shimofuri goby, and is a valuable genomic resource for the study of its evolutionary biology.